IMPLEMENTASI PELAYANAN ADMINISTRASI NIKAH DI KANTOR URUSAN AGAMA (KUA) UJUNG BULU BULUKUMBA MELALUI WEBSITE SIMKAH - Rahmasari, A. Nina; Abd. Halim Talli; Muhammad Anis (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2023)
The Office of Religious Affairs in Ujung Bulu Sub-District has started implementing a marriage registration system through the SIMKAH website by providing guidance to prospective couples to register their marriages in SIMKAH, hoping to facilitate the marriage registration process at the Office of Religious Affairs. This research employs a qualitative research method located at the Office of Religious Affairs in Ujung Bulu Sub-District, Bulukumba Regency, utilizing a juridical and normative Islamic approach based on field observations. Data sources used include observation, interviews, and documentation. The implementation of marriage administration services at the Office of Religious Affairs through the SIMKAH website provides easy access for prospective couples, and the process is relatively quick. The community feels that marriage registration now is very good, especially as it minimizes data falsification, a problem that occurs frequently, and allows for checking identity data errors of prospective couples. The issues or challenges felt by the community and employees at the Office of Religious Affairs in Ujung Bulu Sub-District include network-related problems that can slow down the verification of marriage registration documents.